Pocket Fills for Intrathecal Pump Delivery Systems: A Narrative Review - Banks DW; Jevotovsky DS; Oehlermarx W; Broachwala M; Gulati A; Chakravarthy K (Journal of Pain Research)
Dylan W Banks,1 David S Jevotovsky,1 Whitman Oehlermarx,1 Mustafa Broachwala,2 Amitabh Gulati,3 Krishnan Chakravarthy2 1Department of Physical Medicine and Rehabilitation, New York University, New York, NY, USA; 2Department of Anesthesiology and Pain Medicine, University of California San Diego, San Diego, CA, USA; 3Department of Anesthesiology and Critical Care Medicine, Memorial Sloan Kettering Cancer Center, New York, NY, USACorrespondence: Krishnan Chakravarthy, Department of Anesthesiology and Pain Medicine, University of California San Diego, 3350 La Jolla Village Drive, San Diego, CA, 92161, USA, Email kvc1008@gmail.comAbstract: Intrathecal drug delivery systems (IDDS) are an increasingly common treatment option in the management of refractory chronic pain. IDDS allow for highly customizable administration of medication directly into the intrathecal space, optimizing therapeutic benefit while minimizing systemic side effects. Understanding potential complications of IDDS is key for patient safety. This narrative review examines pocket fills, a potential complication that occurs when inadvertently missing the port on the intrathecal pump reservoir during a pump refill, resulting in the injection of the medication into the surrounding subcutaneous tissue. It is suspected that pocket fill events are vastly underreported and understudied despite posing serious risk for patient safety. Given the limited existing research discussing pocket fills, this narrative review will provide an overview of pocket fills including the anatomy of the intrathecal pump placement, risk factors for pocket fills, preventative techniques, as well as post pocket fill recommendations. Key preventative techniques highlighted include the application of firm pressure throughout the procedure, imaging guidance, as well as post procedure monitoring and device interrogation. As there is a lack of clinical guidelines for pocket fill prevention, we advise tailoring these strategies to available resources and individual patient needs. As IDDS utilization continues to evolve in clinical practice, future quality improvement initiatives could focus on the development of standardized refill protocols, simulation-based training courses and competency assessments, while future research initiatives could focus on comparative analyses of pump refill complication rates under imaging guidance in comparison to template guidance, as well as early detection monitoring technology.Keywords: pocket fill, intrathecal pump, chronic pain, safety